Methodology for the assessment of results in Final Degree Projects of technological areas - Fidias Gerardo Arias Odon (Universitat Politècnica de València, 2018)
This article starts from the problematic that arose when the methodology and evaluation criteria of the Final Degree Projects that are carried out in social sciences are sought to those that are presented in technological areas, without considering the difference between scientific research and technological research. Consequently, the unequal nature of science and technology activities implies different methods and results, which require particular and different criteria to evaluate the technological, whose final products are characterized as material or tangible (hardware) and intangible (software). Specifically, this study aimed to build a methodology for the assessment of results in Final Degree Projects, specifically in technological areas: industrial technologies (manufacturing), information and communication technologies and health technology. Regarding the method used, a documentary research was carried out that consisted of an exhaustive analysis of printed and electronic sources, emphasizing the specialized literature on the subject of technological research and the evaluation of results. As a conclusion of the study, the proposed methodology is presented, which includes the characterization of said works, the definition of indicators and the design of the rubrics for each area.